1948
DOI: 10.1302/0301-620x.30b2.245
|View full text |Cite
|
Sign up to set email alerts
|

Paraplegia in Hyperextension Cervical Injuries With Normal Radiographic Appearances

Abstract: This communication deals solely with a group of cases, hitherto rather obscure, in which damage to the cervical part of the spinal cord occurs without radiographic evidence of vertebral injury or displacement. Two alternative explanations of such injury have been postulated. The first is that the spinal cord pressure is due to acute massive prolapse of an intervertebral disc : but our limited experience of this lesion suggests that as a rule this is recognisable on radiographic examination by narrowing of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
4

Year Published

1958
1958
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(41 citation statements)
references
References 1 publication
1
36
0
4
Order By: Relevance
“…4 The ®ndings in our study are congruous with Schneider's with regard to the etiology, age, presence of cervical spondylosis and the relatively minor injuries sustained. This is in contradistinction to the recent reports by Roth and Penrod in which they described the`heterogenous nature' of patients with traumatic central cord syndrome.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…4 The ®ndings in our study are congruous with Schneider's with regard to the etiology, age, presence of cervical spondylosis and the relatively minor injuries sustained. This is in contradistinction to the recent reports by Roth and Penrod in which they described the`heterogenous nature' of patients with traumatic central cord syndrome.…”
Section: Discussionsupporting
confidence: 63%
“…3 It is generally reported to have a good prognosis for neurologic and functional recovery. 1 It has typically been described to occur most commonly in older persons with cervical spondylosis and hyperextension injuries, without apparent damage to the bony spine, 4 although it may occur at any age with other etiologies, injury mechanisms or predisposing factors. 1,5,6 Postulated mechanisms include squeezing or pinching of the spinal cord both anteriorly and posteriorly, with inward bulging of the ligamentum avum during hyperextension.…”
Section: Introductionmentioning
confidence: 99%
“…Various motion patterns have been hypothesized to cause BFD, including hyperflexion [7], axial rotation [24], and hyperextension [28]. In a classic radiographic study, Allen et al [2] suggested BFD as a flexion-distraction injury, and that the posterior ligaments may fail due to excessive strain, while compression injuries may occur to the anterior vertebral bodies and disc.…”
Section: Introductionmentioning
confidence: 99%
“…6,19 If there is a cord lesion without bony disruption, hyperextension is the most probable mechanism of trauma. 6,24,25 In these instances cervical trauma without bony lesion and malalignment typically affects the C3/C4 (70% 15 ) and the C4/C5 levels. 6,15 Since discoligamentous disruption may be invisible in the radiological evaluation, the clinical findings and the radiological aspect of the cord nevertheless raise the suspicion of discoligamentous insufficiency that usually can be confirmed in the cooperative patient by active dynamic flexion and extension lateral radiographs.…”
Section: Discussionmentioning
confidence: 99%